Arduino-based Reverse Vending Machine Metal Medicine Packaging Exchange - Rebeka Firsly Stephanie Harianja; Lili Rusdiana; Catharina Elmayantie (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2023)
As technology develops, the use of vending machines also develops. In addition to purchasing food and drinks, it can also be used to exchange medicine packaging for coins. To simplify the exchange process to make it more practical and not to spend a lot of time, a reverse vending machine was built for drug packaging containing metal as input. Collecting data using the method of observation and literature study. This type of research is prototyping because the results obtained are in the form of a prototype. This prototype used 3 buttons in main process. The first stage is pressing button 1 to detect metal, then pressing button 2 to weigh, and button 3 to release coins. The test results obtained from the Arduino-Based Reverse Vending Machine Metal Medicine Packaging Exchange indicate that the prototype is able to be used as a medium of exchange for drug packaging trash containing metal into a medium of exchange in money form. The prototype is able to provide a solution for reducing or managing medical trash which contains metal.